Plasma C24:0 ceramide impairs adipose tissue remodeling and promotes liver steatosis and glucose imbalance in offspring of rats - Alberto Camacho-Morales; Lilia G. Noriega; Adriana Sánchez-García; Ivan Torre-Villalvazo; Natalia Vázquez-Manjarrez; Roger Maldonado-Ruiz; Marcela Cárdenas-Tueme; Mariana Villegas-Romero; Itzayana Alamilla-Martínez; Humberto Rodriguez-Rocha; Aracely Garcia-Garcia; Juan Carlos Corona; et al. (Heliyon)
Fetal programming by exposure to high-energy diets increases the susceptibility to type 2 diabetes mellitus (T2DM2) in the offspring. Glucose imbalance during fetal programming might be associated to still unknown selective lipid species and their characterization might be beneficial for T2DM diagnosis and treatment. We aim to characterize the effect of the lipid specie, C24:0 ceramide, on glucose imbalance and metabolic impairment in cellular and murine models. A lipidomic analysis identified accumulation of C24:0 ceramide in plasma of offspring rats exposed to high-energy diets during fetal programing, as well as in obese-T2DM subjects. In vitro experiments in 3T3L-1, hMSC and HUH7 cells and in in vivo models of Wistar rats and C57BL/6 mice demonstrated that C24:0 ceramide disrupted glucose balance, and differentiation and lipid accumulation in adipocytes, whereas promoted liver steatosis. Mechanistically, C24:0 ceramide impaired mitochondrial fatty acid oxidation in adipocytes and hepatic cells, tentatively by favoring reactive oxygen species accumulation and calcium overload in the mitochondria; and also, activates endoplasmic reticulum (ER) stress in hepatocytes. We propose that C24:0 ceramide accumulation in the offspring followed a prenatal diet exposure, impair lipid allocation into adipocytes and enhances liver steatosis associated to mitochondrial dysfunction and ER stress, leading to glucose imbalance.